Licensing of Soil and Greenhouse Fumigation Applicators in Florida - Frederick M. Fishel (EDIS)
PI-136, a 3-page fact sheet by Frederick M. Fishel, explains the law that governs those who make restricted use soil and greenhouse fumigation applications to agricultural crops/soils in Florida. Published by the UF/IFAS Pesticide Information Office, September 2006.